Phenotypic severity in a family with MEND syndrome is directly associated with the accumulation of potentially functional variants of cholesterol homeostasis genes - Barboza Cerda, María Carmen; Barboza Quintana, Oralia; Martínez Aldape, Gerardo; Garza Guajardo, Raquel; Déctor, Miguel Angel (John Wiley & Sons, 2019)
Background: Male EBP disorder with neurologic defects (MEND) syndrome is an X‐linked disease caused by hypomorphic mutations in the EBP (emopamil‐binding protein) gene. Modifier genes may explain the clinical variability among individuals who share a primary mutation. Methods: We studied four males (Patient 1 to Patient 4) exhibiting a descending degree of phenotypic severity from a family with MEND syndrome. To identify candidate modifier genes that explain the phenotypic variability, variants of homeostasis cholesterol genes identified by whole‐exome sequencing (WES) were ranked according to the predicted magnitude of their effect through an in‐house scoring system. Results: Twenty‐seven from 105 missense variants found in 45 genes of the four exomes were considered significant (−5 to −9 scores). We found a direct genotype–phenotype association based on the differential accumulation of potentially functional gene variants among males. Patient 1 exhibited 17 variants, both Patients 2 and 3 exhibited nine variants, and Patient 4 exhibited only five variants. Conclusion: We conclude that APOA5 (rs3135506), ABCA1 (rs9282541), and APOB (rs679899 and rs12714225) are the most relevant candidate modifier genes in this family. Relative accumulation of the deficiencies associated with variants of these genes along with other lesser deficiencies in other genes appears to explain the variable expressivity in MEND syndrome.